The Permeation of High Concentration Hydrogen Sulfide (H2S) Gas Using PTFE (Polytetrafluoroethylene) and PVDF (Polyvinylidene Fluoride) membranes - Asnawati, Asnawati; Diah Ayu Nur Sholehah; Dwi Indarti; Tri Mulyono; Bambang Piluharto; Muflihah, Yeni Maulidah (Department of Chemistry, Faculty of Mathematics and Natural Sciences, University of Jember, 2022)
Hydrogen sulfide (H2S) is a toxic, corrosive, and flammable gas. The presence of H2S gas can be reduced by a permeation method using PTFE (Polytetrafluoroethylene) membranes and PVDF (polyvinylidene fluoride) membranes. This H2S gas passed through the membrane and was then captured by the SAOB (Sulfide Anhydride Oxidant Buffer) in S2- species form. A visible spectrophotometer was applied for the analysis of passed H2S gas. Using a PTFE membrane, the optimum flow rate was obtained at 14.71 mL/min, with a mass flux of 0.825 kg/m2.hour, permeability coefficient of 0.696 kg/m2.hour.bar, and percent removal of H2S gas was 88.14%. The optimum flow rate for the SAOB was obtained at a rate of 0.30 mL/min with a mass flux of 0.843 kg/m2.hour and a percent removal of H2S gas of 89.98%. Based on the results obtained on the PVDF membrane, the mass flux produced in the optimization of H2S gas is 0.742 kg/cm2.hour, and the optimization of the SAOB solution is 0.754 kg/cm2.hour. The resulting permeability coefficient value is 0.741 kg/cm2.hour. The results indicate that this study can remove H2S gas at the optimum H2S gas flow rate of 4.76 mL/minute of 94.89% and the optimum SAOB flow rate of 0.3 mL/minute of 95.66%